'If you put pressure on yourself to produce then that's your responsibility': Mothers' experiences of maternity leave and flexible work in the neoliberal university. Issue 6 (26th November 2018) - Huppatz, Kate; Sang, Kate; Napier, Jemina
Abstract : Women remain underrepresented in senior positions within universities and report barriers to career progression. Drawing on the concepts of Foucault and Bourdieu, with an emphasis on technologies of the self, this article aims to understand mothers' academic career experiences. Interviews were conducted with 35 non‐STEMM (science, technology, engineering, mathematics and medicine) academics in Scotland and Australia, to reveal the gender dimensions of parents' academic careers, in neoliberal university contexts. The data suggest that there are tensions between organizational policies, such as maternity leave and flexible work, and the contemporary demands of academic labour. New managerial discourses which individualize and make use of moral systems are particularly effectual in driving women to take up marketized research activity and compromise leave entitlements.